Mainstreaming orphan millets for advancing climate smart agriculture to secure nutrition and health - Babele, Piyoosh K.; Kudapa, Himabindu; Singh, Yogeshwar; Varshney, Rajeev K.; Kumar, Anil (Frontiers in Plant Science, 2022)
The ever-changing climate and the current COVID-19 pandemic compound the problems and seriously impact agriculture production, resulting in socio-economic insecurities and imposing health implications globally. Most of the poor and malnourished population in developing countries depends on agriculture for food, income, and employment. The impact of climate change together with the COVID-19 outbreak revealed immense problems highlighting the importance of mainstreaming climate-resilient and low input crops with more contemporary agriculture practices. Orphan millets play a vital role in the poor and malnourished population's livelihood, food, and nutrition security. Recognizing their unique potential, the United Nations-Food and Agriculture Organization has announced the year 2023 as the ‘International Year of Millets’. However, despite the unique properties for the present and future agriculture of orphan millets, their cultivation is declining in many countries. As a result, millets have gained attention from researchers which eventually decelerated “multi-omics” resource generation. This review summarizes the benefits of millets and major barriers/ bottlenecks in their improvement. We also discuss the pre-and post- harvest technologies; policies required to introduce and establish millets in mainstream agriculture. To improve and ensure the livelihood of the poor/malnourished population, intensive efforts are urgently needed in advancing the research and development, implementing pre-and post- harvest technological intervention strategies, and making favorable policies for orphan crops to accomplish food and nutrition security. National and international collaborations are also indispensable to address the uncertain effects of climate change and COVID-19.